THEMATIC AND INTEGRATED APPROACH BASED ON ECOPEDAGOGY IN SOCIAL STUDIES LEARNING - Alni Dahlena; Anisa Nurhalimah; Sapriya; Fitriyani, Anindyta (Institut Pendidikan Indonesia, 2025)
Nowadays, Sustainable Development Goals (SDGs), especially the environmental aspect, is a goal that is pursued together, one of which is through learning. This environment-based learning activity can be implemented through ecopedagogy in social studies learning. Ecopedagogy-based learning in social studies can be done through thematic and integrated approaches. This study aims to describe how the thematic approach and integrated approach based on ecopedagogy can be implemented in social studies learning. The research method used in this research is Systematic Literature Review (SLR) with data collection techniques through literature study. The results of this study found that the thematic approach and integrated approach based on ecopedagogy is very suitable and appropriate to use in social studies learning. In addition, thematic and integrated approaches based on ecopedagogy have goals that go hand in hand with the objectives of social studies learning itself.